Feeling New York: Classless urban geographies and affective capitalist reconciliation in Horatio Alger's Ragged Dick. (August 2017) - Wöll, Steffen
Abstract: Acknowledging the productive impulses of the affective turn, this paper examines the affective impacts of urban architecture conveyed by Horatio Alger in his novel Ragged Dick . Without any strict adherence to a particular school of thought, I draw instead on those concepts and theories that promise enriching for an analysis of a nineteenth-century Bildungsroman and its socio-spatial representation of New York's architecture, for instance Central Park and Wall Street. The results underline the flexibility of the affective nexus used in literary geographies, finding the metropolis not as a passive dramaturgical backdrop but as an active agent, whose structural composition works towards the integration of its literary subjects into the affective discourses of its historical period and literary genre. Horatio Alger's Ragged Dick directs this very agency towards the protagonist's integration into the hegemonic structures of sentimentality. In the story, this becomes visible in the mythical abilities of empathy to transcend class divisions and the reconciliatory appeal of the capitalist ideology. Ultimately, affect and emotionality are used to maintain and perform the proper feelings for certain architectural structures, manifesting themselves as a sentimental performance of systemic allegiance. Highlights: Affective structures in Horatio Alger's novel Ragged Dick manifest themselves in the depiction of New York City. Sentiment and affect are employed to express systemic allegiance to unfettered capitalism. Sympathy becomes a commodified discursive power, whose exercise is seen as a privilege of the prosperous. Unchecked capitalism and private compassion merge to form the socio-spatial arrangements of the metropolis.